“The aspectual” Hagiology as the Perspective of the Integration of Research Theological and not Theological - Parzych-Blakiewicz, Katarzyna (Studia Warmińskie, 2019)
In the article is described aspectual hagiology as the proposal of new discipline descending from the classical hagiology. The thesis is developed in five points: the Warmian description of hagiology research, the distinction of notions - the hagiology classical and aspectual; the hagiology specialization in ’the aspect’ (here is sketch of the systematization of the aspectual hagiology in comparison with the classical one: the object, sources, the aim of research, fundamental research), the multidisciplinarity and the transdisciplinarity of the aspectual hagiology and the innovativeness of its research. A subject of study of the classical hagiology is the sainthood as the matter investigated in sources revealed and in the religious ethos of candidates for the altars. The subject of study of the aspectual hagiology includes some elements the sacrum in the culture and belonging to sources of disciplines outside the field of theological researches. Sacrum in culture should be examined by various specialist methods, therefore research on this subject is interdisciplinary. The correlation of interdisciplinary specialist research calls for the creation of two research teams: transdisciplinary and multidisciplinary. Concentration on the hagiological subject as common to different theological and non-theological disciplines leads to the creation of an independent specialization – which the author of the article calls an aspectual „hagiology”. The development of research within the framework of aspectual hagiology is open to social and economic (that is innovative) needs with the preservation of the human dimension.